Tinnitus retraining therapy : - Jastreboff, Pawel J. (Cambridge University Press, 2004)
Tinnitus and oversensitivity to sound are common and hitherto incurable, distressing conditions that affect a substantial number of the population. Pawel Jastreboff's discovery of the mechanisms by which tinnitus and decreased sound tolerance occur has led to a new and effective treatment called Tinnitus Retraining Therapy (TRT). Audiologists, ENT specialists, psychologists and counsellors around the world currently practise this technique, with very high success rates. This book presents a definitive description and justification for the Jastreboff neurophysiological model of tinnitus, outlining the essentials of TRT, reviewing the research literature justifying their claims, and providing an expert critique of other therapeutic practices.